2013
DOI: 10.2174/09298673113209990254
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Glucose Derivatives for Tumor Imaging Using SPECT and PET

Abstract: Glucose is an important molecule for metabolism. It is more actively taken up in tumor cells than in normal cells, thus making it possible to detect the tumor. Radiolabeled glucose derivates have been successfully employed for tumor imaging for several decades. This review focuses on the development of various radiolabeled glucose derivatives as tumor imaging probes with single photon emission computed tomography (SPECT) and positron emission tomography (PET) and discusses basic research data, current status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Both of the techniques are used widely for characterization and measurement of the biological properties at the cellular and molecular levels. 673 The azide−alkyne click reaction is an appropreate reaction and is far better than the conventional methodologies for the development of carbohydrate-based imaging probes for several reasons, such as higher decay-corrected radiochemical yield, higher specific activity, and shorter synthesis time. Synthesis of radiotracers must be rapid and selective and should preserve functional groups on the bioactive molecule.…”
Section: F-labeling In "Carbo-click"mentioning
confidence: 99%
“…Both of the techniques are used widely for characterization and measurement of the biological properties at the cellular and molecular levels. 673 The azide−alkyne click reaction is an appropreate reaction and is far better than the conventional methodologies for the development of carbohydrate-based imaging probes for several reasons, such as higher decay-corrected radiochemical yield, higher specific activity, and shorter synthesis time. Synthesis of radiotracers must be rapid and selective and should preserve functional groups on the bioactive molecule.…”
Section: F-labeling In "Carbo-click"mentioning
confidence: 99%
“…However, aerobic glycolysis in tumor cells may be limited by glucose uptake . Glucose derivatives labeled with various radioactive isotopes and fluorescent dyes have been used to monitor increased glucose uptake associated with a high glycolytic rate in vivo . These include 2‐deoxy‐D‐[1,2‐ 3 H]‐glucose, 2‐deoxy‐D‐[1‐ 14 C]‐glucose, 2‐deoxy‐2‐( 18 F)‐fluoro‐D‐glucose ( 18 F‐FDG) and the fluorescent probe 2‐[N‐(7‐nitrobenz‐2‐oxa‐1,3‐diaxol‐4‐yl)amino]‐2‐deoxyglucose (2‐NBDG) .…”
Section: Conventional Assessment Of Glycolysismentioning
confidence: 99%
“…Generator produced isotopes, such as 99mTc and 68Ga, are readily available and affordable. The availability of a generator and kit chemistry to prepare 99mTc and 68Ga-based molecular probes may have a significant impact on nuclear medicine (Liu et al, 2014 ). It has been shown that 99mTc-glucarate may behave as a suitable alternative to 18F-FDG as a promising breast tumor imaging agent and needs to be further investigated (Gambini et al, 2011 ).…”
Section: Perspectivesmentioning
confidence: 99%